2015
DOI: 10.1021/jacs.5b01493
|View full text |Cite|
|
Sign up to set email alerts
|

A Compact Structure of Cytochrome c Trapped in a Lysine-Ligated State: Loop Refolding and Functional Implications of a Conformational Switch

Abstract: It has been suggested that the alkaline form of cytochrome c (cyt c) regulates function of this protein as an electron carrier in oxidative phosphorylation and as a peroxidase that reacts with cardiolipin (CL) during apoptosis. In this form, Met80, the native ligand to the heme iron, is replaced by a Lys. While it has become clear that the structure of cyt c changes, the extent and sequence of conformational rearrangements associated with this ligand replacement remain a subject of debate. Herein we report a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
164
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(195 citation statements)
references
References 117 publications
(303 reference statements)
14
164
1
Order By: Relevance
“…As expected, the human WT cyt c shows a potential of +252 mV vs. standard hydrogen. The redox potential for cyt c M81A (−19 mV) was over 270-mV more negative than WT cyt c. A similar potential was determined previously for yeast iso-1-cyt c M80A (−80 mV) (20). The potential of cyt c M81H (−69 mV) suggests a stabilization of the oxidized cytochrome, similar to the chemically generated horse heart bis-His cyt c variant (+41 mV) (11); such a change is often observed when substituting a stronger histidine ligand for methionine.…”
Section: Electron Paramagnetic Resonance Spectroscopy Of Cyt C Axial supporting
confidence: 84%
See 1 more Smart Citation
“…As expected, the human WT cyt c shows a potential of +252 mV vs. standard hydrogen. The redox potential for cyt c M81A (−19 mV) was over 270-mV more negative than WT cyt c. A similar potential was determined previously for yeast iso-1-cyt c M80A (−80 mV) (20). The potential of cyt c M81H (−69 mV) suggests a stabilization of the oxidized cytochrome, similar to the chemically generated horse heart bis-His cyt c variant (+41 mV) (11); such a change is often observed when substituting a stronger histidine ligand for methionine.…”
Section: Electron Paramagnetic Resonance Spectroscopy Of Cyt C Axial supporting
confidence: 84%
“…In addition, pronounced peaks are present at 2.08 and 1.97 in human cyt c M81A. These are also observed in the yeast iso-cyt c M81A variant, albeit with weaker intensity (20,21). Human cyt c M81H exhibits g values at 2.91, 2.29, and 1.58, very similar to a cytochrome b562 M7H with bisHis ligands to b heme and bis-imidazole-ligated hemin (23) ( Table S3).…”
Section: Electron Paramagnetic Resonance Spectroscopy Of Cyt C Axial mentioning
confidence: 78%
“…The dynamics of the heme coordination loop have been thoroughly characterized for yeast iso -1 cyt c . 40 Further, many of its previously characterized mutants, including M80K # from our recent work, 21 facilitate analysis of the ligation to the heme iron.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of cyt c mutants have revealed that His, Lys, and hydroxide ligands give rise to very similar positions of the Soret band, blue-shifted by a few nm from its position at 409 nm for the Met-ligated WT*. 17,21,4345 The far-UV and near-UV CD spectra of Met-SO and native cyt c (Figure S2) suggest only minor perturbations in the secondary and tertiary structure by the modification. Thus the ligation by His26, 33, or 39 residues, which are remote from the heme coordination loop, is unlikely.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation